Multidimensional Perfectionism among Medical, Dental and Optometry students at SEGi University, Malaysia - Rebecca Shin Yee Wong; Nazrila Shaherah Fadhulah Suhaimi; Mun-Kit Low; Muhammad Azhar Ahmad; Renuthuyilarasi Thavachelvan; Zainah Sakhnini; Shaima Ahmed Ali (Universitas Ahmad Dahlan, 2018)
Perfectionism is a double-edged sword: it may act as a motivational force in its adaptive state or it may bring many harmful effects in its maladaptive state. Currently, perfectionism is viewed as a multidimensional construct with three orientations: self-oriented perfectionism (SOP), other-oriented perfectionism (OOP) and socially-prescribed perfectionism (SPP). This cross-sectional study explored the multidimensional perfectionism of medical, dental and optometry at SEGi University, Malaysia using the Multidimensional Perfectionism Scale (MPS). Medical students scored significantly higher than both dental and optometry students in the SOP subscale (p<0.05). International students had a significantly higher mean SOP subscale score than the local students, whereas those from the higher income group had a significantly higher mean SOP subscale score than those from the lower income group (p<0.05). The high achievers, on the other hand, had a higher mean SOP subscale score than the non-high achievers (p<0.05). Further exploration on the psychological impact of perfectionism on the students is recommended in future studies.